Exploring the Destiny and Distribution of Thiocyanate in the Water-Soil-Plant System and the Potential Impacts on Human Health - Arancibia-Miranda, N; Arancibia-Miranda, N; Manquian-Cerda, K; Manquian-Cerda, K (Elsevier B.V., 2022)
Endocrine disruptors like thiocyanate are some of the principal causes of chronic disorders worldwide. Prenatal and postnatal exposure to thiocyanate can interfere with normal neurological development in both fetuses and newborns. Currently, little information regarding thiocyanate levels and potential sources of exposure is available. In this study, we evaluated thiocyanate uptake and accumulation in chard and spinach grown under greenhouse conditions. Both chard and spinach are commonly used to produce baby foods. Three thiocyanate concentrations were compared: Control, T1 (30 ng mL−1), and T2 (70 ng mL−1). Thiocyanate accumulation depended on the concentration and exposure time. Chard was found to accumulate more thiocyanate than spinach, with leaf accumulation > stem accumulation (p < 0.0194) and maximum concentrations of 76 ng g−1 (control), 112 ng g−1, (T1), and 134 ng g−1 (T2). The estimated daily intake (EDI) of thiocyanate for chard and spinach (fresh) exceeded the subchronic reference dose of 200 ng−1 kg−1 day−1 and the chronic reference dose of 600 ng−1 kg−1 day−1. In addition, the EDI of thiocyanate for spinach in baby food exceeded twice the chronic reference dose in the vulnerable newborn–1 year age group. However, all EDIs were lower than the lowest observed adverse effect level (LOAEL) of 1.9 × 105 ng kg−1 day−1. Further studies are needed that increase our knowledge of thiocyanate levels and potential environmental sources to reduce opportunities for exposure, especially in vulnerable groups. © 2022